Accuracy of presepsin in neonatal sepsis: systematic review and meta-analysis. Issue 4 (3rd April 2019) - Parri, Niccolò; Trippella, Giulia; Lisi, Catiuscia; De Martino, Maurizio; Galli, Luisa; Chiappini, Elena
ABSTRACT: Introduction : Neonatal sepsis represents a major cause of morbidity and mortality in neonates. No diagnostic test has been demonstrated to be sufficiently accurate to confirm or exclude neonatal sepsis. This study aimed to evaluate the diagnostic accuracy of presepsin (P-SEP) for neonatal sepsis. Areas covered : A systematic review of literature was performed on Medline and EMBASE. A meta-analysis was performed to calculate pooled sensitivity, specificity, diagnostic odds ratio (DOR), and summary receiver operating characteristic of P-SEP for neonatal sepsis. Eight studies were included, involving 636 neonates. Pooled sensitivity and specificity were 0.90 and 0.90, respectively. The pooled DOR was 120.94, and the Area Under Curve (AUC) was 0.968, indicating a high level of diagnostic accuracy. Using cut-off values <600 ng/L, sensitivity reached 0.93, with a specificity of 0.81 and AUC 0.8195, while using a threshold >600 ng/L, sensitivity was 0.87 and specificity 0.97, with higher diagnostic accuracy (AUC 0.976). Significant heterogeneity was found between studies. Expert commentary : Diagnostic accuracy of P-SEP resulted high in detecting neonatal sepsis. Even though it cannot be recommended as a single diagnostic test, P-SEP could be a helpful and valuable biomarker in neonates with suspected sepsis.